ER–/PR+ subset of invasive breast carcinoma (IBC): a distinct phenotype with good prognosis - Simona Stolnicu (Polish Journal of Pathology, 2018)
The expression of the estrogen (ER) and progesterone (PR) receptors in IBC patients represents a well-know prognostic and predictive factor. The existence of ER–/PR+ as a distinct phenotype, however, is controversial as well as is its prognostic significance. The aim of the study was to assess the incidence and prognosis in patients with ER–/PR+ IBC. One hundred and twelve patients with IBC were analyzed regarding ER/PR profile and survival. GraphPad prism 6 for Windows and Kaplan Mayer curve were used to determine overall survival (OS) and disease-free survival (DFS), with p < 0.05 as statistically significant. Of the 112 IBC patients, 75% were ER+/PR–, 16.07% were ER–/PR–, 7.14% were ER+/PR– and only 1.78% were ER–/PR+. OS was 100% in the ER–/PR+ group and 91.6% in the ER+/PR+ group. The lowest OS was found in the ER-/PR- group (72.2%), while OS was 100% in ER–/PR+ group. Regarding DFS, there were no statistically significant differences in the four groups (p = 0.11), although the highest DFS was found in the ER–/PR+ group (100%). ER–/PR+ tumors were associated with younger age (p = 0.72), smaller tumor diameter (p = 0.27), absence of lymph node metastases, and HER2 overexpression. Our results suggest that ER–/PR+ cases represent the rarest phenotype in IBC cases but its association with the best OS and DFS in other ER/PR phenotypes indicates an independent predictive value of PR for treatment considerations.